Environmental DNA detection tracks established seasonal occurrence of blacktip sharks (Carcharhinus limbatus) in a semi-enclosed subtropical bay - Postaire, Bautisse D.; Bakker, Judith; Gardiner, Jayne; Wiley, Tonya R.; Chapman, Demian D. (Scientific reports, 2020)
The integration of eDNA analysis into the population assessment and monitoring of sharks could greatly improve temporal and spatial data used for management purposes. This study aimed to compare eDNA detection against well-established seasonal changes in blacktip shark ( Carcharhinus limbatus ) abundance in Terra Ceia Bay (FL, USA). We used a species-specific real-time PCR approach to detect C. limbatus eDNA in the bay on a near monthly basis from spring through mid-fall in 2018 and 2019. Previous studies have shown that C. limbatus give birth in the bay in early summer and immature sharks occur there until late fall, when decreasing water temperatures cause them to move offshore and southwards. Water samples (2 L) were collected (4–6 per month) and filtered in the field, with each then being subjected to real-time PCR. Carcharhinus limbatus ‘positive’ filters were significantly more commonly collected during the April-July sampling period than during the August-October sampling period. While following the predicted pattern, eDNA concentration was generally too low for accurate quantification. Our results show that C. limbatus eDNA detection follows known seasonal residency patterns consistently over 2 years of monitoring. Species-specific eDNA analysis using real-time PCR could therefore represent a cost-effective, scalable sampling tool to facilitate improved shark population monitoring in semi-enclosed marine habitats.